Analisa Spasial Risiko Longsoran Skala Kecamatan, Studi Kasus di Kecamatan Kaliwiro, Kabupaten Wonosobo - Raharjo, Puguh Dwi; Hidayat, Edi; Widiyanto, Kristiawan; Puswanto, Eko; Winduhutomo, Sueno (Pusat Survei Geologi, 2017)
Subdistricts of Kaliwiro - Wonosobo is a region with diverse topography and included in the Karangsambung Geological Nature Reserve. The purpose of this study was to determine the role of socio-community in Karangsambung which influencing the landslides risk. In this study, we analyted every environmental physical factors to give the landslide hazard map. Analytical Hierarchy Process (AHP) is used as a method to processing landslides maps using Geographic Information System (GIS). The landslides hazard associated with the socio-community and the environment, visible role in reducing the landslides risk. The results obtained that in some places have a high-level of landslide hazard. However, the socio-community is very well in overcoming the impact and mitigation of landslides. Social conditions is very influential on the landslides risk which often occur in the Kaliwiro Sub district. Keywords: GIS, lanslide, menace, vulnerability, capacity, risk.